Differences in self-perceptions of aging across the adult lifespan: the sample case of awareness of age-related gains and losses - Kaspar, Roman; Schilling, Oliver; Diehl, Manfred; Gerstorf, Denis; Rupprecht, Fiona S.; Sabatini, Serena; Wahl, Hans-Werner (Psychology and aging, 2023)
Rooted in the premises of lifespan developmental theory, the concept of awareness of age-related change (AARC) posits that growing older comes with both experiences of gains and losses across different behavioral domains. However, little is known about how age-related change is perceived across the entire adult lifespan, provided that respective measures can be validly compared. Further, few studies have adopted an approach that examines gains and losses simultaneously to study a potential shift in the ratio of perceived age-related gains and losses from adolescence to advanced old age. Using cross-sectional data from the German Socio-Economic Panel, this study tested the measurement invariance of the 10-item AARC short form and examined age differences in the awareness of age-related changes across 1,612 participants aged 16-93 years. First, partial measurement invariance of the AARC-Gains and AARC-Losses scales was established, allowing for valid group comparisons across young adulthood, midlife, and old age. Second, results indicated that people experience more AARC-Gains than AARC-Losses throughout the adult lifespan. However, older adults exhibited an increasingly less favorable gains-to-losses ratio, primarily driven by more loss experiences. Gain experiences were mostly stable across age groups. Third, differences in levels of AARC were related to individuals’ background characteristics relevant at the respective time of life, such as education (early adulthood), employment (midlife), and social resources (old age). These results highlight the utility of considering a broad age range when examining the nature and correlates of age differences in perceived age-related gains and losses. (PsycInfo Database Record (c) 2023 APA, all rights reserved)